Agronomic efficiency of rock phosphates, partially acidulated phosphates and thermalphosphates in a cerrado soil - Rein, Thomaz A.; Souza, Djalma M.G. de (Pesquisa Agropecuaria Brasileira, 2014)
Eighteen phosphorus sources (phosphates) produced from Araxá, MC, Pato de Minas, MC, Tapir; MC, Catalão, GO and Anitápolis, SC, rock phosphates were evaluated during four years. The test crop was soybeans and the relative agronomic efficiency was calculated using as reference the triple superphosphate response curve obtained from one application in the first year. The rock phosphates applied in natura exhibited low agronomic efficiency which almost did not increase with time. The solubility and relative efficiency of the partially acidulated phosphates was directly proportional to the acidulation rate (H+/P2O5 molar ratio), and were not dependent on te rock phosphate origem The fused and calcinated thermalphosphates exhibited high agronomic efficiency. The citric acid or neutral ammonium citrate + water extractant solutions allowed to predict with a good approximation the agronomic efficiency of te phosphates, mainly of te partially acidulated.